First-principles generated mechanical property database for multi-component Al alloys: Focusing on Al-rich corner - Wang J.; Du Y.; Tao X.; Ouyang Y.; Zhang L.; Chen Q.; Engström A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Systematic first-principles calculations of the single crystal elastic stiffness constants (cij’s) and the polycrystalline aggregates including bulk modulus (B), shear modulus (G), Young’s modulus (E) have been performed for series binary and ternary Al compounds at 0 K. In addition, the temperature-dependent elastic properties for some technologically important phases are calculated. The cij’s are calculated by means of an efficient strain-stress method. Phonon density of states or Debye model is employed to calculate the linear thermal expansion, which is then used to calculate the temperature dependence of elastic properties. The calculated temperature-dependent elastic properties are compiled in the format of CALPHAD (CALculation of PHAse Diagram) type formula. The presently computed elastic properties for Al compounds are needed for simulation of microstructure evolution of commercial Al alloys during series of processing route.